Conversational Patterns and Listener Responses Associated With an Enhanced Fading Affect Bias After Social Disclosure. (October 2019) - Muir, Kate; Brown, Charity; Madill, Anna
The fading affect bias (FAB) is a phenomenon of autobiographical memory whereby negative emotions associated with event memories fade in intensity over time more than positive emotions. Social disclosure enhances the FAB and listener responsiveness during social disclosure is an important facet; however, little is known about the nature of listener verbal responses that facilitate an enhanced FAB. In this study, we used discourse analysis to explore listener verbal responses and conversational patterns associated with an enhanced FAB after social disclosure—backchanneling, in which the listener shows they are paying attention to the story underway; displays of understanding whereby the listener shows awareness of the speaker's emotional state; and positive facilitation, characterized by mutual development of positive interpretations of both pleasant and unpleasant experiences. We suggest that such listener responses are similar to those described in the verbal person-centered framework, and the emotional benefits of social disclosure are in part collaboratively created by conversationalists.